Rethinking Radical Inclusiveness: A Theoretical Provocation - Teguh Wijaya Mulya (ANIMA Indonesian Psychological Journal, 2016)
The notions of human rights and identity politics have been widely drawn on in the contemporary understandings and practices of developing more inclusive cities. Examining the UN Habitat III Issue Paper on Inclusive Cities (2015), in this article I attempt to identify and problematize some assumptions that might have underpinned our efforts to improve the inclusiveness of our cities. I argue that a liberal view of human being has constrained the understandings about who “everyone” is, the nature of their sense of self, and what they want; which subsequently might exclude and marginalise those who do not fit our conceptions. Alternatively, I will draw on poststructuralist theorisation of discourse and subjectivity to offer a new way of thinking about human rights and identity politics, and discuss how it might contribute to our understanding and practices of inclusiveness.